Cigarette Smoking Impairs Pancreatic Duct Cell Bicarbonate Secretion - Kadiyala, Vivek; Lee, Linda S; Banks, Peter A; Suleiman, Shadeah; Paulo, Joao A; Wang, Wei; Rosenblum, Jessica; Sainani, Nisha I; Mortele, Koenraad; Conwell, Darwin Lewis (JOP. Journal of the Pancreas, 2013)
Objective To compare pancreatic duct cell function in smokers (current and past) and never smokers by measurement of secretin-stimulated peak bicarbonate concentration ([HCO3-]) in endoscopic collected pancreatic fluid (PF). Methods This retrospective study was cross-sectional in design, recording demographic information (age, gender, etc.), smoking status (former, current, never), alcohol intake, clinical data (imaging, endoscopy), and laboratory results (peak PF [HCO3-]) from subjects evaluated for pancreatic disease at a tertiary pancreas center. Univariate and multivariate statistical analysis (SAS Version 9.2, Cary, NC, USA) was performed to assess the relationship between cigarette smoking and secretin-stimulated pancreatic fluid bicarbonate concentration. Results A total of 131 subjects underwent pancreatic fluid collection (endoscopic pancreatic function test, ePFT) for bicarbonate analysis: 25.2% (33 out of 131) past smokers, 31.3% (41 out of 131) current smokers, and 43.5% (57 out of 131) were never smokers. Measures of Association: The mean peak PF [HCO3-] in never smokers (81.3±18.5 mEq/L) was statistically higher (indicating better duct cell function) when compared to past smokers (66.8±24.7 mEq/L, P=0.005) and current smokers (70.0±20.2 mEq/L, P=0.005). However, the mean peak [HCO3-] in past smokers was not statistically different from that in current smokers (P=0.575), and therefore, the two smoking groups were combined to form a single “smokers cohort”. When compared to the never smokers, the smokers cohort was older (P=0.037) and had a greater proportion of subjects with definite chronic pancreatitis imaging (P=0.010), alcohol consumption ≥20 g/day (P=0.012), and abnormal peak PF [HCO3-] (P<0.001). Risk-Based Estimates: Cigarette smoking (risk ratio, RR: 2.2, 95% CI: 1.3-3.5; P<0.001), diagnosis of definite chronic pancreatitis imaging (RR: 2.2, 95% CI: 1.6-3.2; P<0.001) and alcohol consumption ≥20 g/day (RR: 1.6, 95% CI: 1.1-2.4; P=0.033) were all associated with low mean peak PF [HCO3-] (indicating duct cell secretory dysfunction). Multivariate Analysis: Smoking (odds ratio, OR: 3.8, 95% CI: 1.6-9.1; P=0.003) and definite chronic pancreatitis imaging (OR: 5.7, 95% CI: 2.2-14.8; P<0.001) were determined to be independent predictors of low peak PF [HCO3-], controlling for age, gender, and alcohol intake. Furthermore there was no interaction between smoking status and alcohol intake in predicting duct cell dysfunction (P=0.571). Conclusion Measurement of pancreatic fluid bicarbonate in smokers reveals that cigarette smoking (past and current) is an independent risk factor for pancreatic duct cell secretory dysfunction (low PF [HCO3-]). Furthermore, the risk of duct cell dysfunction in subjects who smoked was approximately twice the risk (RR: 2.2) in never smokers. Further in depth, translational research approaches to pancreatic fluid analysis may help unravel mechanisms of cigarette smoking induced pancreatic duct cell injury. Image: Comparison of mean peak pancreatic fluid [HCO3-] and 95% CI among all studied cohorts.